2012
DOI: 10.5539/ass.v8n4p143
|View full text |Cite
|
Sign up to set email alerts
|

Malaysian Graduates English Adequacy in the Job Sector

Abstract: Historically, the use of the English Language in Malaysia, then Malaya, dates back to the Colonial times. This shows there has been a legacy of English usage in the nation. Recently, in view of globalization and increasing competition among nations in the world, there has been a renewed emphasis on the importance of English. This study hopes to provide some feedback from four industries in Kemaman about the adequacy of our new graduates. This study focused on two GLCs and two private sector companies in Kemama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…The most cited explanation was "most employers hire fluent English speakers", "English proficiency is important to impress employers" and "ideal job requires English language skills". This has been cited by studies on English language and employment in Malaysia in the past two decades, such as, Ball and Chik (2001), Sarudin et al (2008), Lim (2010), Sekharan Nair et al (2012), Roshid andChowdhury's (2013), andSelvaratnam (2019). All these studies agreed that English language proficiency was crucial for employment in Malaysia and now with this study's participants nodding in unison as well.…”
Section: English Language Enables Highersupporting
confidence: 74%
See 2 more Smart Citations
“…The most cited explanation was "most employers hire fluent English speakers", "English proficiency is important to impress employers" and "ideal job requires English language skills". This has been cited by studies on English language and employment in Malaysia in the past two decades, such as, Ball and Chik (2001), Sarudin et al (2008), Lim (2010), Sekharan Nair et al (2012), Roshid andChowdhury's (2013), andSelvaratnam (2019). All these studies agreed that English language proficiency was crucial for employment in Malaysia and now with this study's participants nodding in unison as well.…”
Section: English Language Enables Highersupporting
confidence: 74%
“…On English language and employment opportunities in Malaysia, Sekharan Nair et al (2012) investigated the possibility of lack of English proficiency contributing to poor market value among new graduates in Malaysia as well as to identify the aspects of the language proficiency skills that was most favored by the Malaysian work sector. The results surmised that the lack of English proficiency might lead to occupational segregation and affected employment prospects in Malaysia.…”
Section: Existing Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…It is fairly obvious that ESL students have little opportunity to use English outside the classroom, especially in the non-English language. According to Krishnan et al (2012), curriculum designers and policymakers should take a look at the current curriculum, which focuses on workbook drilling to learn grammatical precision. Students are being deprived of this form of learning when it comes to real-world communication.…”
Section: Poor Speaking Skills Among Esl Learnersmentioning
confidence: 99%
“…Overall, extensive research has shown that undergraduate students have low proficiency (i.e. not up to the desired levels) in the English language (Ismail, 2011;Musa et al, 2012;Nair et al, 2012, Rusli et al, 2018. The language competence of Malaysian undergraduates is still a long way from satisfactory level though they have learned English for 11 to 13 years in schools (David et al, 2015).…”
Section: Study Settingmentioning
confidence: 99%